6 - How to Research the Changing Outlines of African Livelihoods: by Leo J. de Haan & Annelies Zoomers - de Haan, Leo J. (Africa Development, 2006)
This paper examines how to research the changing outlines of African liveli- hoods in the present era of globalisation. After an analysis of the historical and theoretical context in which the modern livelihood approach developed, two trends in modern livelihood studies are discussed, i.e. its increased holistic features and the surmounting of its micro-orientation. Subsequently, the most pressing issues in livelihood research are reviewed: decomposition of house- holds, and the increased diversification and increased multi-locality of liveli- hoods under globalisation. The next section focuses on two major theoretical and methodological challenges facing the livelihood approach at present. First, with respect to the problem of access, we will demonstrate that the livelihood approach can become more powerful analytically by improving its theoretical depth through incorporating valuable elements of sovereignty and power. Sec- ond, there is the access to livelihood opportunities in relation to decision-mak- ing. In this context, we review various relevant concepts, such as livelihood strategies and styles, in order to operationalise the improved theoretical depth. We then propose livelihood trajectories as an appropriate methodology for ex- amining pathways of African livelihoods. In doing so, the paper also suggests an agenda for future research on African livelihoods.